PENGARUH KAMPANYE PADA YOUTUBE WEB SERIES TROPICANA SLIM “SORE-ISTRI DARI MASA DEPAN” TERHADAP SIKAP GAYA HIDUP SEHAT MAHASISWA PERGURUAN TINGGI SWASTA DI KOTA BANDUNG - Siska Merdekawati; Martha Tri Lestari (Dialektika, 2018)
Nowadays, the digital media, especially social media gives a huge influence on the marketing world. This is where YouTube has become popular as a social media and regards as one of media platforms since many companies nowadays creating content marketing. Tropicana Slim, a company that has applied the content marketing trough YouTube in a format web series with the title "SORE-Istri Dari Masa Depan”. Web series is a shorter series of narratives that use the internet as a medium for its spread. Web series "SORE-Istri Dari Masa Depan" is one of the web series that has an interesting message that is campaigning healthy lifestyle for young people. Thus, this research is aimed to examine the influence of Campaign on YouTube Tropicana Slim web series “SORE-Istri Dari Masa Depan” to The Attitude of healthy lifestyle of private college students in Bandung City. This study was divided into two independent variables and one dependent variable. The first independent variable was campaign (X1), the second independent variable was YouTube Video (X2), and the dependent variable was Attitude (Y). This research uses quantitative method with descriptive analysis and multiple linear regression. Sampling using nonprobability sampling method with 100 respondents coming from three largest private universities in Bandung City, Universitas Pasundan, Universitas Telkom and Universitas Komputer Indonesia. Based on descriptive analysis, the result revealed that the response of respondents as a whole were in a very good category. It can be seen that there was a significant influence of Campaign on YouTube Tropicana Slim web series "SORE- Istri Dari Masa Depan" to The Attitude of healthy lifestyle of private college students in Bandung City.